Managing knowledge in software method adoption. (19th July 2005) - Mathiassen, Lars; Vogelsang, Lasse
The complex and problematic relationship between software development methods and practices is well documented. Methods are difficult to adopt. There are several barriers toward successfully bringing methods to practice, and practices are, by the end of the day, quite different from method prescriptions. Methods are, however, continually developed, and organisations spend considerable resources trying to improve practices through adoption of new methods. We know relatively little about the long-term dynamics involved in such adoption efforts. This research reports from a three-year effort within an IT department of a large multinational company in which a new method was first introduced, then used to support organisation-wide projects, and subsequently extended based on emerging practices. The study applies two complementary knowledge management perspectives – networks and networking – to interpret the experiences from the case. The study reveals how method perceptions and approaches shift radically through different stages of software method adoption.